2017
DOI: 10.1111/jfd.12621
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA)

Abstract: Koi herpesvirus (KHV) causes KHV disease (KHVD). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti-KHV antibodies have not yet been fully validated for KHV. Therefore, it was developed and validated an enzyme-linked immunosorbent assay (ELISA) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…The principle of the PCR method, including nested PCR and real‐time TaqMan PCR (Bergmann et al., 2006; Gilad et al., 2002, 2004; Gray et al, 2002K Yuasa et al., 2012; Yuasa et al., 2005), is the amplification of viral DNA so that the result can be visualized. Yet, it is difficult to isolate KHV in the tissue of sick fish for the first time; the nucleic acid detection method, which is based on genes such as TK and Sph, often gives a negative result, even in fish that were previously infected or lived with dying fish (Bergmann et al., 2017). If fish are infected with KHV a long time ago and that may keep persistent or latent infections, the virus could not be detected because the amount of KHV is too little.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of the PCR method, including nested PCR and real‐time TaqMan PCR (Bergmann et al., 2006; Gilad et al., 2002, 2004; Gray et al, 2002K Yuasa et al., 2012; Yuasa et al., 2005), is the amplification of viral DNA so that the result can be visualized. Yet, it is difficult to isolate KHV in the tissue of sick fish for the first time; the nucleic acid detection method, which is based on genes such as TK and Sph, often gives a negative result, even in fish that were previously infected or lived with dying fish (Bergmann et al., 2017). If fish are infected with KHV a long time ago and that may keep persistent or latent infections, the virus could not be detected because the amount of KHV is too little.…”
Section: Discussionmentioning
confidence: 99%
“…The general principle behind the ELISA is the confirmation of antigen or antibody with a measurable substrate. PCR or real‐time PCR is false‐negative usually (Bergmann et al., 2017). The success rate of virus isolation in cell culture is very low (States & Dna, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors ( 2 ) have suggested this may be due to increasing cellular rather than humoral mechanisms of resistance; however, other non-specific protective mechanisms (i.e., trained immunity) could also be involved (see discussion below). This non-specific expansion would explain the existence of false positives on fish serological diagnosis in many reports ( 6 , 11 13 , 15 , 16 ) and most of the difficulties experienced with the use of recombinant fragment for serodiagnosis ( 6 ), which made the use of whole CyHV-3 the best method to estimate specific carp antibodies for diagnostic purposes ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay sera dilutions have proven useful in CyHV-3 serodiagnosis for identifying samples with specific antibodies that range from 300- to 2,500-fold dilution end points. CyHV-3-specific antibodies in infected-survivor sera tend to have relatively high titers of >1,600-fold ( 4 ), and titers as high as 62,500-fold have been reported 1 year after natural exposure ( 2 ) or as high as 76,800-fold have been reported 8 weeks after experimental infection ( 17 ). When sera dilutions of <2,500-fold are used, cross-reactions with CyHV-1 have been observed in some ( 2 , 4 ) but not all reports ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current detection methodology relies on polymerase chain reaction (PCR) to confirm the diagnosis (Gilad et al., 2002). Recently, an enzyme‐linked immunosorbent assay (ELISA) as a serological tool was demonstrated to have high sensitivity and specificity and particularly useful at the pond and farm levels (Bergmann et al., 2017). There is currently no effective method for treatment; therefore, the prevention and control of KHV infection can only be achieved using vaccines, biosecurity measures or breeding (OIE, 2016).…”
Section: Introductionmentioning
confidence: 99%